Inhibitory potential of lactobacilli against Escherichia coli internalization by HT 29 cells - Bujňáková, Dobroslava; Kmeť, Vladimír (Folia microbiologica, 2012)
A quantitative fluorescent in situ hybridization method was employed to evaluate the competitive inhibitory effect of three Lactobacillus strains (Lactobacillus reuteri, Lactobacillus gasseri, and Lactobacillus plantarum) against Escherichia coli internalization in a model system of HT 29 cells. Furthermore, aggregation and adhesion abilities of the Lactobacillus strains were examined. All lactobacilli were able to attach to the HT 29 cells and aggregate with pathogens; however, the adhesion and aggregation degree was strain-dependent. L. reuteri possessed a high capacity of adhesion (6.80 ± 0.63; log CFU ± SEM per well), whereas lower capacities were expressed by L. gasseri (4.52 ± 0.55) and L. plantarum (4.90 ± 0.98). Additionally, L. reuteri showed the rapid or normal ability to aggregate with selected E. coli in comparison with remaining two lactobacilli, which showed only slow or negative aggregative reaction. Internalization of E. coli into the cell lines was markedly suppressed by L. reuteri, while L. gasseri and L. plantarum caused only a minimum anti-invasion effect. The fact that L. reuteri in our experiments showed an outstanding potential for adhering to the colon epithelial cell line, compared with the rest strains, suggested that one of the possible mechanisms of preventing pathogen adhesion and invasion is simple competitions at certain receptors and capability to block receptor binding sites, or that an avid interaction between L. reuteri and the host cell might be modulating intracellular events responsible for the E. coli internalization. Moreover, L. reuteri exhibited a strong ability to aggregate with E. coli, which could be another limiting factor of pathogen invasion.
Keywords: Models, Biological; biologické modely; bakteriální adheze; Escherichia coli; Epithelial Cells; epitelové buňky; HT29 Cells; lidé; Humans; Bacterial Adhesion; buňky HT-29; Lactobacillus